Pengaruh Pemberian Media Video Bullying di Sekolah terhadap Pengetahuan dan Sikap di MTs Waru Sukoharjo: The Effect of Providing Bullying Video Media in Schools on Knowledge and Attitudes at MTs Waru Sukoharjo - Khoyriani, Nadila Anti Nur; Werdani, Kusuma Estu (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Bullying in schools is a serious global problem, so it is of concern to the public. However, not many schools have provided bullying education. The number of bullying cases among teenagers is increasing every year in Indonesia. However, there have not been many efforts to provide education by schools to teenagers, including MTs Waru Sukoharjo. This activity aims to provide education to students about the dangers of bullying so that there is an increase in students' knowledge and attitudes towards bullying at MTs Waru Sukoahrjo. This community service activity was carried out using video media to provide counseling to students. The video contains the meaning of bullying, types of bullying, factors that influence bullying, the role of teachers in dealing with bullying, and strategies for handling bullying. Service activities are carried out by giving a pre-test, then giving video media and a post-test. The results of community service activities show that video media about bullying has proven successful in increasing students' knowledge and attitudes. This is indicated by an increase in student scores with the average knowledge before and after providing video media amounting to 6.67 to 7.31. Meanwhile, the increase in the average attitude before and after providing video media was 23.36 to 24.02. Based on the results of the Wilcoxon statistical test on knowledge and attitudes, shows a value of p = 0.000 (p <0.05). Thus, it shows that there is an influence of providing video media on students' knowledge and attitudes about bullying at MTs Waru Sukoharjo.